Improving SMEs Business Productivity with Microsoft Excel Training in the Big Data Era - Yuningsih, Yuningsih; Andriani, Lis; Firdaus, Luthfi; Nugroho, Dwi; Putra Pradipta, Rafi (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2024)
The business complexity requires business actors to have special skills in managing and analyzing data in Big Data. This community service aims to provide in-depth training on the use of Microsoft Excel as a platform for managing and analyzing data. The ability to manage and analyze data will greatly affect business productivity in facing the challenges and opportunities that exist in the Big Data era. Participants will be equipped with knowledge and practical skills in utilizing various relevant Excel features, including pivot tables, vlookup, if, and sophisticated data analysis techniques. This training uses a mentoring approach through several processes: preparation, implementation, mentoring and evaluation, and post training mentoring. The results reveal significant effects: awareness of technology to increase SMEs productivity is built; the competence of SMEs actors in using Microsoft Excel increases; and SMEs actors are able to increase efficiency and effectiveness in managing, processing, and analyzing data so that they can optimize the decision-making process more effectively and accurately. However, in-depth material is still needed, so further training is needed to deepen the knowledge and skills of SMEs actors. This is important for SMEs to respond to the challenges in the increasingly complex global market.